The Role of Factor XI in Thrombin Generation Induced by Low Concentrations of Tissue Factor - Keularts, Irene M. L. W.; Zivelin, Ariella; Seligsohn, Uri; Hemker, H. Coenraad; Béguin, Suzette (Thrombosis and Haemostasis, 2001)
Thrombin generation has been studied in the plasma of severely factor XI deficient patients under conditions in which contact activation did not play a role. In platelet-rich as well as platelet-poor plasma, thrombin generation was dependent upon the presence of factor XI at tissue factor concentrations of between 1 and 20 pg/ml i.e. ~ 0.01 to 0.20% of the concentration normally present in the thromboplastin time determination. The requirement for factor XI is low; significant thrombin generation was seen at 1% factor XI; at 10%, thrombin formation was nearly normalised. A suspension of normal platelets in severely factor XI deficient plasma did not increase thrombin generation. This implies that there is no significant factor XI activity carried by normal platelets, although the presence of factor XI and factor XI inhibitors in platelets cannot be ruled out.
Keywords: Factor XI; thrombin generation; platelet procoagulant activity; tissue factor